Benralizumab (anti-IL5Rα) depletes gut tissue eosinophilia and improves symptoms in hypereosinophilic syndrome with gastrointestinal involvement - Kuang, Fei Li; Alao, Hawaa; Kumar, Sheila; Powers, Astin; Quezado, Martha; Wang, Zengfeng; Ware, JeanAnne; Wetzler, Lauren; Brown, Thomas; Khoury, Paneez; Klion, Amy D. (Journal of allergy and clinical immunology, 2018)
Methods Twenty symptomatic HES subjects on stable background therapy with persistent eosinophilia (AEC >=1000 cells/mm3) were enrolled in a phase 2 double-blind placebo-controlled trial of benralizumab. Post-treatment at week 24, AEC was 0 cells/mm3 in all subjects and endoscopies demonstrated dramatic depletion of eosinophils: median 0 eos/hpf in all upper GI segments (range 0-3 eos/hpf, n=7) and colon (range 0-1 eos/hpf, n=5).